2019
DOI: 10.1016/j.artd.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and pulmonary fat embolism after unilateral total knee arthroplasty

Abstract: Fat embolism syndrome is the presence of a fatty embolus in the circulatory system that can manifest itself in multiple ways, ranging from asymptomatic presentation to respiratory failure, neurocognitive deficits, and death. It is a relatively common complication after procedures or conditions such as orthopaedic surgery, severe burns, liver injury, closed-chest cardiac massage, and liposuction. This pathology is relatively common in the field of orthopaedics, especially in long bone fractures and procedures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, later studies with larger study populations have shown that while avoiding intramedullary instrumentation does not significantly reduce the incidence of fat embolisation during TKA,25 26 it may reduce the embolic load 27. Cerebral fat embolism has also been reported after standard TKA,4 28 but there is a lack of studies comparing technology-assisted and standard instrumented TKA. Alternatively, fat emboli may arise from other parts of the surgery such as impaction of the femoral and tibial implants, but this is unlikely to differ between technology-assisted and conventionally instrumented TKA 25–27…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies with larger study populations have shown that while avoiding intramedullary instrumentation does not significantly reduce the incidence of fat embolisation during TKA,25 26 it may reduce the embolic load 27. Cerebral fat embolism has also been reported after standard TKA,4 28 but there is a lack of studies comparing technology-assisted and standard instrumented TKA. Alternatively, fat emboli may arise from other parts of the surgery such as impaction of the femoral and tibial implants, but this is unlikely to differ between technology-assisted and conventionally instrumented TKA 25–27…”
Section: Discussionmentioning
confidence: 99%